p38 Mitogen-activated protein kinase stabilizes mRNAs that contain cyclooxygenase-2 and tumor necrosis factor AU-rich elements by inhibiting deadenylation. - Dean, J; Sarsfield, S; Tsounakou, E; Saklatvala, J (2003)
AU-rich elements (AREs) in 3'-untranslated regions of mRNAs confer instability. They target mRNAs for rapid deadenylation and degradation and may enhance decapping. The p38 MAPK pathway stabilizes many otherwise unstable ARE-containing mRNAs encoding proteins involved in inflammation; however, the mRNA decay step(s) regulated by the signaling pathway are unknown. To investigate whether it regulates deadenylation or the decay of the mRNA body, we used a tetracycline-regulated beta-globin mRNA reporter system to transcribe pulses of mRNA of uniform length. We measured on Northern gels the migration of reporter mRNAs isolated from cells transfected only with reporter plasmid or co-transfected with an active mutant of MAPK kinase-6, and treated either with or without the p38 MAPK inhibitor SB 203580. Differences in migration were shown by RNase H mapping with oligo(dT) to be due to poly(A) shortening. Insertion of an ARE into the beta-globin reporter mRNA promoted rapid deadenylation and decay of hypo-adenylated reporter mRNA. p38 MAPK activation inhibited the deadenylation of reporter mRNAs containing either the cyclooxygenase-2 or tumor necrosis factor AREs. The regulation of deadenylation by p38 MAPK was found to be specific because deadenylation of the beta-globin reporter mRNA either lacking an ARE or containing the c-Myc 3'-untranslated region (which is not p38 MAPK-responsive) was unaffected by p38 MAPK. It was concluded that the p38 MAPK pathway predominantly regulates deadenylation, rather than decay of the mRNA body, and this provides an explanation for why p38 MAPK regulates mRNA stability in some situations and translation in others.